Quality and Affordable Education through Quality Management Systems in Higher Education - Muhammad Afif Hasbullah; Nisaul Barokati Selirowangi; Mohammad Syaiful Pradana; Buyun Khulel; Moh Hudi (EDUTEC : Journal of Education And Technology, 2020)
The general goal of education is to develop Indonesian people completely in the sense that carried out education still maintain unity, diversity and develop individual’s ideals. Every citizen has the right to obtain education equally with excellence and a balance (equity) between the utilization (access) with achievement. The higher education system must be able to create a quality higher education that is also affordable by the people of Indonesia. A university leader must be in-line and lead a "quality revolution". All energy and attention are focused on the "quality revolution". For this reason, this paper will examine the Implementation of Higher Education Quality Management Systems. As a case study is that has implemented a Quality Management System. According to Law No. 12 of 2012 concerning Higher Education. Quality Higher Education is Higher Education that produces graduates who are able to actively develop their potential and produce Science and / or Technology that is useful for the Community, nation, and country. The government operates a higher education quality assurance system to get quality education. The Higher Education quality assurance system referred to consists of: a. internal quality assurance system developed by Higher Education; and b. external quality assurance system carried out through accreditation. Implementation of Quality Management Systems in Higher Education can produce Quality and Affordable Education.